Neonatal intrahepatic cholestasis caused by citrin deficiency in two Malaysian siblings: outcome at one year of life - Thong, M.K.; Boey, Christopher Chiong Meng; Sheng, J.S.; Ushikai, M.; Kobayashi, K. (2010)
We report two Malaysian siblings with neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD). The younger sibling, a six-month-old Chinese girl, presented with prolonged neonatal jaundice, and was investigated for biliary atresia. Urine metabolic screen showed the presence of urinary-reducing sugars, and she was treated with a lactose-free formula. NICCD was suspected based on the clinical history, examination and the presence of urinary citrulline. Mutation study of the SLC25A13 gene showed the compound heterozygotes, 851del4 and IVS16ins3kb, which confirmed the diagnosis of NICCD in the patient and her three-year-old female sibling, who also had unexplained neonatal cholestasis. Longterm dietary advice, medical surveillance and genetic counselling were provided to the family. The diagnosis of NICCD should be considered in infants with unexplained prolonged jaundice. DNA-based genetic testing of the SLC25A13 gene may be performed to confirm the diagnosis retrospectively. An awareness of this condition may help in early diagnosis using appropriate metabolic and biochemical investigations, thus avoiding invasive investigations in infants with neonatal cholestasis caused by NICCD.